2016
DOI: 10.5755/j01.ee.27.3.15395
|View full text |Cite
|
Sign up to set email alerts
|

Tendencies and Relations of Defense Spending and Economic Growth in the EU Countries

Abstract: European countries are surrounded by growing conflicts and security threats. For every country it is necessary to ensure internal and external security. Defense should be seen as preventative spending as well as like an insurance policy. In terms of that, many policy makers have to decide how much money should be spent on defense. This paper investigates the tendencies and relationships of defense spending and economic growth in the European Union (EU) countries taking into consideration the level of countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The results revealed that high level of economic growth will leads to less spending on military. Our findings are supported by (Dudzeviciute, Peleckis, & Peleckiene, 2016). Result shows that income inequality negatively affects the military expenditures.…”
Section: Results Of Military Expendituressupporting
confidence: 76%
“…The results revealed that high level of economic growth will leads to less spending on military. Our findings are supported by (Dudzeviciute, Peleckis, & Peleckiene, 2016). Result shows that income inequality negatively affects the military expenditures.…”
Section: Results Of Military Expendituressupporting
confidence: 76%
“…Granger causality is not identical to causation in the classical philosophical sense, but it does demonstrate the likelihood of such causation or the lack of such causation more forcefully than does simple correlation (Stern, 2011). Granger causality test estimates the following two regression equations (Shahbaz et al , 2013; Farzanegan, 2014; Dudzevičiūtė et al , 2016): where p is the number of lags; β , the parameter; ε , the error.…”
Section: Empirical Evidence and Research Methodologymentioning
confidence: 99%
“…Similarly, if the p parameters β 2, i are jointly significant then the null hypothesis that y does not Granger cause x can be rejected. Granger causality test is based on the concept of causal ordering and assumption as follows: a variable x is said to Granger cause another variable y if the past values of x help predict the current level of y given all other appropriate information (Stern, 2011; Dudzevičiūtė et al , 2016).…”
Section: Empirical Evidence and Research Methodologymentioning
confidence: 99%
“…Granger causality demonstrates the likelihood of the causation or the lack of such causation more forcefully than does simple correlation (Stern, 2011). Granger causality test is expressed by the following two regression equations (Shahbaz et al, 2013;Mehmood, 2013;Gokmenoglu et al, 2015;Dudzevičiūtė et al, 2016):…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, if the p parameters  2,i are jointly significant then the null hypothesis that y does not Granger cause x can be rejected. Granger causality test is based on the concept of causal ordering and assumption as follows: a variable x is said to Granger cause another variable y if past values of x help predict the current level of y given all other appropriate information (Stern, 2011;Dudzevičiūtė et al, 2016).…”
Section: Methodsmentioning
confidence: 99%